EVALUATION OF ROCK MASS QUALITY BASED ON ROCK MASS RATING AND GEOLOGICAL STRENGTH INDEX METHOD FOR TUNNEL CONSTRUCTION IN PIYUNGAN-PATUK AREA, YOGYAKARTA SPECIAL PROVINCE, INDONESIA - , phanthoudeth pongpanya ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The tunnel excavation plan is proposed to solve the transportation problem in Piyungan-Patuk area, which is located in the eastern part of Yogyakarta special province, Indonesia. This tunnel will be built in the area that contains various types of rock, i.e. andesitic lava, andesitic breccias, pumiceous breccias and tuffaceous sandstone. Before this underground structure will be constructed, the main problems that may occur during the excavation need to be considered which relating to rock mass instabilities. Thus, to minimize and avoid those problems, it is necessary to do the detail site investigation related to geological conditions in order to estimate the rock mass quality in this area. This research is mainly aimed to evaluate the rock mass quality by applying two empirical methods such as Rock Mass Rating (RMR) and Geological Strength Index (GSI). The purpose of RMR system is to classify the quality of rock mass by using surface and subsurface (borehole) data, in order to guide the excavation method and also to give the recommendation of tunnel supports as well as the unsupported span and stand-up time. Furthermore, GSI system is not only aimed to estimate the rock mass quality, but also the modulus of deformation (Ed), compressive strength (Ïc) and tensile strength (Ït) of the rock mass. Moreover, according to RMR and GSI method, the relationship between RMRbasic and GSI rating is able to conduct in form of linear equation in order to compare the rock mass quality condition between both methods. Besides, depended on the rock mass conditions in the study area, this research has also tried to figure out the engineering potential risks that may occur during the tunnel construction and attempted to suggest the appropriate method to control and prevent such those potential risks. Based on RMR determination by using surface data, the qualities of rock masses in the study area are classified to be good and fair rock, the good rocks are found on andesitic lava and andesitic breccias (RMR=62-77, unsupported span is 8.3 m, stand-up time is 333.33 days)